Usando visualização para possibilitar a análise simultânea de documentos na aplicação da técnica coding - Boiça Neto, Arlindo Leal (Universidade Federal de São Carlos, 2012)
Qualitative research seeks to understand a specific subject through descriptions, comparisons and interpretations of the data, which are represented by words, pictures, videos and sounds. In the context of qualitative research were treated in more detail in this work, the steps of data collection and analysis. In step analysis of the data coding technique is used which has a test procedure whereby data is divided, and highly integrated to form a theory. The task involving coding technique when done manually requires a lot of research. Moreover, the tools found supporting the technical coding does offer features that let you work with several documents at once, which would facilitate the task of the researcher in the analysis and data management. This paper presents the iCode, a free tool that supports the technical coding, allowing the coding of multiple documents simultaneously, referenced here as simultaneous coding. Using this tool, we intended to reduce the coding time through the use of visualization and information management. It is intended to facilitate the analysis of the data using the visual metaphor Treemap, to enable management of multiple documents simultaneously. We conducted a feasibility study to assess whether it is feasible to apply the tool to create codes and categories, ie, apply the coding technique using differential functionality that the tool provides, which is the fact that it can handle multiple documents at once. This viability was observed for the efficiency and effectiveness of the participants in the application of manual coding technique, coding simultaneously using the tool iCode and coding each document separately, using the tool iCode. The feasibility study evaluated whether the simultaneous coding is beneficial regarding the coding of a document at a time. The results provide evidence that the simultaneous coding done using the tool iCode, the technique facilitates coding, reducing time spent on your driving, making its implementation more agile.
Keywords: Engenharia de software; Teoria da codificação; Pesquisa qualitativa; Visualização de software; Técnica treemap; Técnica Coding; Ferramenta Treemap; Coding technique; Qualitative research; Visualization software; Treemap technique; Treemap tool; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO